“Citizens of Heaven” versus “The Islamic Peril” - Nancy L. Stockdale (International Institute of Islamic Thought, 2004)
In early 2001, the Holy Land Experience (HLE) theme park opened in Orlando, Florida. Before 9/11, Islam was merely a shadowy figure at the HLE; after 9/11, however, the park has promoted a vision of Islam and Muslims that fosters hate among American Protestant visitors. This paper argues that the HLE is a site of extreme potential danger, for it espouses holy war and dissent between American Christians, Jews, and Muslims.